Assessment of the Carrying Capacity of Integrated Pond Aquaculture of Portunus trituberculatus at the Ecosystem Level - Dong, Shipeng; Wang, Fang; Zhang, Dongxu; Yu, Liye; Pu, Weijia; Xu, Xian; Xie, Yicheng (Frontiers in Marine Science, 2021)
In recent years, integrated pond aquaculture with artificial enhancements has been crucial in improving the supply of aquatic products and ensuring food safety. This study constructed two trophic models of integrated pond aquaculture ecosystems of P. trituberculatus– Marsupenaeus japonicus (PM) and P. trituberculatus– M. japonicus– Sinonovacula constricta (PMS) using Ecopath with Ecosim software. The energy flows, ecosystem properties, and carrying capacities of the two ecosystems were analyzed and evaluated. The results showed that the ecotrophic efficiency values in the binary PM and ternary PMS ecosystems were 0.962 and 0.954 for P. trituberculatus and M. japonicus and 0.952 for S. constricta. The effective trophic levels of P. trituberculatus and M. japonicus were 2.065 and 2.027 in the PM system, and those of P. trituberculatus, M. japonicus, and S. constricta were 2.057, 2.018, and 2.010 in the PMS system. The primary productivities of the PM and PMS ecosystems were 2623.79 g/m2/240 d and 2781.48 g/m2/240 d, with 2.13% and 37.83% of the energy flowing to trophic level II and 97.87% and 62.17% flowing to the detritus, respectively. The total energy of the detritus group was 2900.89 g/m2/240 d and 2372.98 g/m2/240 d, with 931.02 g/m2/240 d and 1505.35 g/m2/240 d flowing to trophic level II, respectively. The total primary production/total respiration ratio of the PMS ecosystem (1.632) was lower than that of the PM ecosystem (4.824), indicating that the former had a greater degree of exploitation. At the current feeding level, the carrying capacities of P. trituberculatus and M. japonicus were 65.15 and 47.62 g/m2 in the PM ecosystem, and those of P. trituberculatus, M. japonicus, and S. constricta were 64.96, 48.06, and 100.79 g/m2 in the PMS ecosystem, respectively. At adequate feeding levels, the carrying capacities of P. trituberculatus and M. japonicus were 83.76 and 48.52 g/m2 in the PM ecosystem and 81.82 and 53.44 g/m2 in the PMS ecosystem. The ecotrophic efficiency values and energy flow parameters of the two integrated pond aquaculture ecosystems indicated that S. constricta was a suitable collocation culture species for P. trituberculatus and M. japonicus, and there is room for improvement in the aquaculture ecosystem.